Comparative study on Headless Shell-On (HLSO) Black Tiger Shrimp (Penaeus monodon) processing under on board and land based factory facilities (Bangladesh Journal of Zoology, 2021)
Shrimps is one of the main export commodities of the country and earns about more than 40 crores 47 lac US $in 2017. Black Tiger (BT) shrimp alone contributes about 67 % to the total shrimp export per year. Aquaculture shrimps are being processed in the land-based processing plant while wild catch is being processed onboard (fishing vessels) in the Bay of Bengal. A study was conducted to compare the yield and economic loss/gain of headless shell-on (HLSO) shrimp during processing by labor and crews at onboard (sea) and land based (land) factories. A total of twelve samples were examined; six for land and six for sea that was designated as “P” and “V”, respectively. After beheading to produce HLSO, individual shrimp weight was measured. The average weight of an individual BT was 50.25 ± 4.174 g for V and 51.13 ±3.66 g for P. Average yield from individual shrimp was 1.19 g higher in P compared to V. Found 23.10 g less production from 1 kg BT in V compare to P which is statistically significant (P=0.057). Our estimated results indicated that one vessel got 649.89 Kg less product valued BDT 1,381,016 compare to land based processing plants due to processing by crews on board. Whole scenario predicts that more economic loss if we consider for 37 shrimp trawlers in operation.Bangladesh J. Zool. 48(2): 393-398, 2020